Interleukin‐8, but not the Related Chemokine CXCL1, Sustains an Autocrine Circuit Necessary for the Properties and Functions of Thyroid Cancer Stem Cells. (21st September 2016) - Liotti, Federica; Collina, Francesca; Pone, Emanuela; La Sala, Lucia; Franco, Renato; Prevete, Nella; Melillo, Rosa Marina
Abstract: Interleukin‐8 (IL‐8/CXCL8) mediates its biological effects through two receptors, CXCR1 and CXCR2. While CXCR1 recognizes IL‐8 and granulocyte chemotactic protein‐2, CXCR2 binds to multiple chemokines including IL‐8, CXCL1, 2 and 3. Both IL‐8 and CXCL1 have been implicated in the neoplastic features of thyroid cancer (TC). Here, we assessed the role of the autocrine circuits sustained by IL‐8 and CXCL1 in determining TC stem cell (TC SC) features. Using immunohistochemistry, we found that thyroid epithelial cancerous, but not normal, cells stained positive for IL‐8, whose levels correlated with lymph‐nodal metastases. We assessed the expression of endogenous IL‐8 and CXCL1, by ELISA assays, and of their receptors CXCR1 and CXCR2, by flow cytometry, in a panel of TC cell lines. These molecules were expressed in TC cell lines grown in adherence, and at higher levels also in thyrospheres enriched in stem‐like cells. RNA interference demonstrated that IL‐8/CXCR1, but not CXCL1/CXCR2, is crucial for the sphere‐forming, self‐renewal and tumor‐initiating ability of TC cells. Accordingly, treatment of TC cells with IL‐8, but not with CXCL1, potentiated cell stemness. We identified CD34 as an IL‐8‐induced gene and as a TC SC marker, since it was overexpressed in thyrospheres compared to adherent cells. Moreover, CD34 is required for the efficient sphere‐forming ability and tumorigenicity of TC cells. Our data indicate that IL‐8, but not the CXCL1 circuit, is critical for the regulation of TC SCs, and unveils novel potential targets for the therapy of as yet untreatable forms of TC. Stem Cells 2017;35:135–146 Abstract : IL‐8 is critical for the sphere formation, self‐renewal and tumor‐initiating ability of thyroid cancer stem cells. Targeting the IL‐8/CXCR1 circuit could be exploited as a novel therapeutic strategy for patients with untreatable thyroid carcinoma.